Analysis of the Hospital Preparedness Index in Responding to Disasters Based on the Hospital Safety Index and Its Influencing Factors at RSUD Haji Makassar: Análisis del índice de preparación hospitalaria para responder a desastres basado en el índice de seguridad hospitalaria y sus factores influyentes en RSUD Haji Makassar - Al Habsyi, Magfirah; Rivai, Fridawaty; Zulkifli, A.; Thamrin, Yahya; Irwandy, Irwandy; Sari, Nurmala (Gaceta Médica de Caracas, 2026)
Aims: This study aimed to assess the disaster preparedness of RSUD Haji Makassar using the Hospital Safety Index (HSI) framework. Materials and Methods: A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were obtained using the HSI questionnaire, which focused on hospital facilities and infrastructure, while qualitative data were collected through purposive sampling involving in-depth interviews with key informants. Four key informants participated in this study, comprising Occupational Health and Safety (OHS) staff and Non-Medical Facilities Maintenance Installation staff, with the OHS Committee serving as a triangulation.